Factors Predicting Habitat Suitability for the Occurrence of Gaur Using Ensemble Modeling in Chitwan National Park of Nepal - Kafle, Kamal; Yadav, Shailendra Kumar; KC, Nishan; Dhami, Bijaya; Neupane, Bijaya; Joshi, Rajeev; Timilsina, Sachin; Adhikari, Binaya; Miya, Mahamad Sayab; Adhikari, Saraswoti; Gaire, Damodar; Adhikari, Hari (Journal of Agriculture and Forestry University, 2026)
Gaur, a large herbivore native to South and Southeast Asia, supports ecosystem health by enhancing soil sustainability, promoting plant growth, and aiding plant succession. In Nepal, their presence is limited to the protected habitats of two lowland (Terai) protected areas: Chitwan National Park (CNP) and Parsa National Park (PNP). However, information on the habitat factors influencing Gaur occurrence is limited, yet is essential for improving the existing habitats of this keystone species and prioritizing conservation efforts within the protected area. To address this gap, our study used an ensemble modelling approach to predict Gaur habitat suitability and identify key factors influencing their occurrence in CNP, Nepal. To gather data on Gaur's presence points, field-based surveys were conducted in April and May 2021, including periodic censuses and annual monitoring. Their presence was verified through direct observations, identification of pellet droppings, and hoofmarks found within the park. Ensemble modeling identified approximately 183.53 km2 within the CNP as highly suitable habitat for Gaur, representing 2.1% of the buffer zone and 97.9% of the core area. Of the 33 variables used to construct the habitat suitability model, human population density, slope, and livestock density were the most influencing factors. For long-term Gaur conservation, our study recommends prioritizing habitat management by strictly limiting human activities and livestock grazing in the core of CNP.